Introduction to the Special Issue on Wars and Disasters: Advancing Care during Times of Crisis - Leopoldo C. Cancio (MDPI AG, 2024)
Civilian mass-casualty disasters and armed conflict share many features, including the fact that both maximally challenge multidisciplinary burn teams. Rigorous training is required to build teams and systems that can respond effectively. One of the critical but potentially overlooked components of readiness for crisis care is a robust clinical research program. Rather than stalling progress, disasters and conflict over the last 100 years consistently energized advances in care. This was made possible by the hard work of our predecessors to learn from the crisis in the midst of the crisis, and resulted in significant reductions in postburn mortality. Now, further work is needed not only to maintain these improvements in mortality, but also to understand the long-term functional outcomes and to improve the quality of life of burn survivors. Clinical research programs to address these issues must be established now, so that we are optimally prepared for the next conflict or disaster.